Uma experiência sobre o ensino da matemática no ensino médio sob a perspectiva da utilização de problemas da OBMEP - Guimarães, João Paulo Silva (Universidade Federal de São Carlos, 2020)
In this work we present the idealization, application and discussion of the use of 5 OBMEP problem versions in the form of activity sheets using manipulable material and technological resources in mobile phones.
An experience about the teaching of mathematics in high school under the perspective of the use of OBMEP problems
Keywords: OBMEP; Ensino médio; Fichas de atividades; Excel; Saresp; Geogebra; High school; Activity sheets; OUTROS